The role and position of the indonesian medical discipline honorary council in the fair resolution of medical disputes - Setiaji, Sigit; Isharyanto, Isharyanto; Sulistiyono, Adi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
The primary objective of this study is to provide a comprehensive description of the role and position of the Medical EthicsCouncil of Indonesia (MKDKI) in facilitating the equitable resolution of medical disputes within the Indonesian context. Thepresent study constitutes a normative legal research. The research findings indicate that the resolution of medical disputes shouldbe channelled through MKDKI, as it possesses the necessary expertise in the application of professional discipline within themedical field. Furthermore, MKDKI is an authoritative institution responsible for determining whether a doctor has violatedprofessional disciplinary standards. The term "can" as stipulated in Article 66 paragraph (1) of Law Number 29 of 2004regarding Medical Practise encompasses the possibility of either initiating a complaint against MKDKI or refraining fromdoing so. Legal confusion may occur, thus necessitating the replacement of the word "can" with "must." This implies thatcomplaints regarding medical issues must be resolved through MKDKI as a mandatory step. It is imperative to conduct ajudicial review of Article 66, paragraph (1) of Law Number 29 of 2004 pertaining to Medical Practise. Additionally, it isessential to deliberate on the authority of the Medical Council of Indonesia (MKDKI) in determining compensation for disputingparties. In order to ensure legal clarity for both medical practitioners and the general public, it is imperative that every decisionmade by the MKDKI (Medical Knowledge and Decision-making Institute) is carefully considered.Keywords: Medical Disputes; MKDKI; Doctors